Effects of Fluid Shear Stress on Human Intervertebral Disc Nucleus Pulposus Cells Based on Label-Free Quantitative Proteomics. (14th September 2022) - Xie, Liang-yu; Cao, Sheng-nan; Li, Zi-teng; Wang, Dan-dan; Shi, Bin
Abstract : Objective . To explore the possible mechanism of fluid shear stress on human nucleus pulposus cells based on label-free proteomics technology. Methods . The human nucleus pulposus cell line was purchased and subcultured in vitro. The Flexcell STR-4000 multiflow field cell fluid shear stress loading culture system was used to apply continuous laminar fluid shear stress (12 dyne/cm 2, 45 mins) to the monolayer adherent cells. Those without mechanical loading were used as the control group, and those subjected to fluid shear loading were used as the experimental group. Differential protein expression was identified using mass spectrometry identification technology, and bioinformatics analysis was performed using Gene Ontology GO (Gene Ontology) and Kyoto Encyclopedia of Genes and Genomes KEGG (Kyoto Encyclopedia of Genes and Genomes). Results . The proteomics results of the experimental group and the control group showed that the total number of mass spectra was 638653, the number of matched mass spectra was 170110, the total number of identified peptides was 32050, the specific peptide was 30564, and the total number of identified proteins was 4745. Comparing the two groups, 47 proteins were significantly differentially expressed, namely, 25 upregulated proteins and 22 downregulated proteins. Bioinformatics analysis showed that significantly different proteins were mainly manifested in cellular process, biological regulation, metabolic process, binding, catalytic activity, cellular components (cell part), organelle part (organelle part), and other molecular biological functions. Conclusion . Using proteomics technology to screen human nucleus pulposus cells after fluid shear stress loading, the differential protein expression provides a basis for further exploration of the mechanism of mechanical factors on nucleus pulposus.